2021
DOI: 10.1016/j.jss.2021.02.037
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and the Cholecystitis Experience at a Major Urban Safety-Net Hospital

Abstract: Background Acute cholecystitis is a common reason for emergency general surgery admission. The declaration of the COVID-19 pandemic may have resulted in treatment delays and corresponding increases in severity of disease. This study compared cholecystitis admissions and disease severity pre- and post-declaration of pandemic. Materials and Methods Retrospective review of adult acute cholecystitis admissions (1/1/20-5/31/20). Corresponding time periods in 2018 and 2019 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Most nonacute CCEs were performed in patients who were previously treated for CDL and had nonbearable pain spells or suspicion for malignancy. While Vallès et al [27] reported a decrease in Grad I (mild) cholecystitis, we did not see a difference regarding overall caseload, timing of presentation, and severity of disease of our cholecystitis patients during the lockdown. The perception of the local hospital’s situation may have a hard-to-calculate influence on primary care physicians in their decision to admit a patient for surgery or treat medically.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Most nonacute CCEs were performed in patients who were previously treated for CDL and had nonbearable pain spells or suspicion for malignancy. While Vallès et al [27] reported a decrease in Grad I (mild) cholecystitis, we did not see a difference regarding overall caseload, timing of presentation, and severity of disease of our cholecystitis patients during the lockdown. The perception of the local hospital’s situation may have a hard-to-calculate influence on primary care physicians in their decision to admit a patient for surgery or treat medically.…”
Section: Discussioncontrasting
confidence: 87%
“…They reported a decrease in admission for cholelithiasis during the early lockdown with an increase in admission for cholelithiasis between late May and the end of June 2020 [26]. Others have also reported reduced rates of cholecystitis during the lockdown [4, 27], which is interesting in light of increased weight gain [28, 29] and substance use during these time periods [30]. The south of Germany was hit hard and early by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one exception is the significantly higher percentage of SSI during the COVID time period, the reasons for which are unclear. A study at an urban, safety-net hospital in Boston also observed a 49% decrease in admissions for cholecystitis 27 . However, when stratified by severity, only admissions for Tokyo I mild cholecystitis declined significantly 27 .…”
Section: Discussionmentioning
confidence: 95%
“…However, when stratified by severity, only admissions for Tokyo I mild cholecystitis declined significantly 27 . The authors concluded that not all cases of acute cholecystitis progress to more severe disease and some mild cases resolve with outpatient antibiotics or symptomatic treatment 27 .…”
Section: Discussionmentioning
confidence: 98%